Chiral separation of cathinone derivatives using β‐cyclodextrin‐assisted capillary electrophoresis–Comparison of four different β‐cyclodextrin derivatives used as chiral selectors - Hägele, Johannes S. (Electrophoresis, 2019)
In the past decade, more than 100 different cathinone derivatives slopped over entire Europe due to their enormous popularity. Generally, these novel psychoactive substances are easily available via the internet. This fact leads to various social problems, since cathinones are substances with consciousness‐changing effects and are mainly misused for recreational matters by their consumers. Cathinones possess a chiral center including two enantiomeric forms with potentially different pharmacological behavior. This fact makes analytical method development regarding their chiral separation indispensable. In this study, a chiral capillary zone electrophoresis method for the enantioseparation of 61 cathinone and pyrovalerone derivatives was developed by means of four different β‐cyclodextrin derivatives. As chiral selectors, native β‐cyclodextrin as well as three of its derivatives namely acetyl‐β‐cyclodextrin, 2‐hydroxypropyl‐β‐cyclodextrin, and carboxymethyl‐β‐cyclodextrin were used. The cathinone and pyrovalerone derivatives were either purchased in internet stores or seized by police. As a result, overall 58 of 61 studied substances were partially or baseline separated by at least one of the four chiral selectors using 10 mM of β‐cyclodextrin derivative in a 10 mM sodium phosphate buffer (pH 2.5). Furthermore, the method was found to be suitable for simultaneous enantioseparations, for enantiomeric purity checks and to differentiate between positional isomers. Moreover, an intra‐ and an interday validation was performed successfully for each chiral selector to prove the robustness of the method.